CFD experiments on a low crested sloping top caisson breakwater. Part 2. Analysis of plume impact. (1st February 2019) - Buccino, Mariano; Daliri, Mohammad; Dentale, Fabio; Calabrese, Mario
Abstract: Walkden et al. (2001) showed that severe impact events could be generated at the inner face of a sloping top caisson breakwater, as a consequence of violent wave overtopping. The authors employed the pressure impulse theory proposed by Cooker and Peregrine (1995), to develop a method capable of predicting the magnitude and distribution of loadings at the wall. It was finally recognized air trapped between the overtopping jet and the structure to have a primary role in transferring momentum to the free surface of the protected basin. Unfortunatey, that pioneering study was carried out using only 3 individual waves, with identical height and period; accordingly, no systematic analysis of this fascinating phenomenon could be provided. This paper employs results of full scale CFD experiments to fill this gap. The research outcomes, consistent with the Walkden et al. (2001) findings, suggest that the occurrence of impulsive loadings at the inner face of the breakwater is intimately correlated to the occurrence of impact pressures onto the outer wall, due to breaking waves. A physically based correction of the Walkden et al. theory has been proposed, which allows to get reasonable estimates of the pressure impulse under both quasi standing and breaking waves.